Defoliation‐induced compensatory transpiration is compromised in SUT4‐RNAi Populus. (28th September 2020) - Harding, Scott A.; Frost, Christopher J.; Tsai, Chung‐Jui
Abstract: The tonoplast sucrose transporter PtaSUT4 is well expressed in leaves of Populus tremula  ×  Populus alba (INRA 717‐IB4), and its inhibition by RNA‐interference (RNAi) alters leaf sucrose homeostasis. Whether sucrose partitioning between the vacuole and the cytosol is modulated by PtaSUT4 for specific physiological outcomes in Populus remains unexplored. In this study, partial defoliation was used to elicit compensatory increases in photosynthesis and transpiration by the remaining leaves in greenhouse‐grown poplar. Water uptake, leaf gas exchange properties, growth and nonstructural carbohydrate abundance in source and sink organs were then compared between wild‐type and SUT4 ‐RNAi lines. Partial defoliation increased maximum photosynthesis rates similarly in all lines. There was no indication that source leaf sugar levels changed differently between wild‐type and RNAi plants following partial defoliation. Sink levels of hexose (glucose and fructose) and starch decreased similarly in all lines. Interestingly, plant water uptake after partial defoliation was not as well sustained in RNAi as in wild‐type plants. While the compensatory increase in photosynthesis was similar between genotypes, leaf transpiration increased less robustly in RNAi than wild‐type plants. SUT4‐RNAi and wild‐type source leaves differed constitutively in their bulk modulus of elasticity, a measure of leaf turgor, and storage water capacitance. The data demonstrate that reduced sucrose partitioning due to PtaSUT4 ‐RNAi altered turgor control and compensatory transpiration capacity more strikingly than photosynthesis and sugar export. The results are consistent with the interpretation that SUT4 may control vacuolar turgor independently of sink carbon provisioning.